Efficacy and acceptability of third-wave psychotherapies in the treatment of depression: a network meta-analysis of controlled trials - Schefft, Cora; Heinitz, Christian; Guhn, Anne; Brakemeier, Eva-Lotta; Sterzer, Philipp; Köhler, Stephan (Frontiers in Psychiatry, 2023)
Introduction In recent decades, various new psychotherapy approaches have been developed in an effort to overcome issues of non–response, referred to as “third–wave psychotherapies”. How third–wave therapies perform in comparison to each other, to classical CBT, or other common comparators in the treatment of depression has not yet been systematically assessed. Methods We firstly determined the scope of the term “third–wave” by conducting a systematic search. The identified approaches were then used as search terms for the systematic review and network meta–analysis (NMA). We searched MEDLINE, CENTRAL, PsychINFO and Web of Science from inception until July 31, 2022. We assessed randomized controlled trials comparing third–wave psychotherapies to each other, CBT, treatment as usual (TAU), medication management, active control conditions, or waitlist (WL) in adult populations with depressive disorders. The treatments included were acceptance and commitment therapy, behavioral activation, cognitive behavioral analysis system of psychotherapy, dialectical behavioral therapy, mindfulness-based cognitive therapy, meta-cognitive therapy, positive psychotherapy and schema therapy. The primary outcome was depression severity (efficacy) at study endpoint, and the secondary outcome was all–cause discontinuation (acceptability). Results Of 7971 search results, 55 trials were included in our NMA (5827 patients). None of the third–wave therapies were more efficacious than CBT but most were superior to TAU (standardized mean differences (SMD) ranging between 0.42 (95% CI -0.37; 1.19) and 1.25 (0.48; 2.04)). Meta–cognitive therapy (MCT) was more efficacious than three other third-wave therapy approaches . None of the third–wave treatments were more acceptable than WL or CBT. Twenty-seven percent of the trials were rated as low risk of bias. Confidence in the evidence was largely low according to GRADE. Inconsistency emerged for a small number of comparisons. Interpretations Third–wave therapies are largely efficacious and acceptable alternatives to CBT when compared to TAU, with few differences between them. The evidence so far does not point towards superiority or inferiority over CBT. Patient–level research may offer possibilities for tailoring individual psychotherapies to the needs of individual patients and future trials should make this data available. The evidence base needs to be broadened by sufficiently powered trials.